Specialized immune responses in the peritoneal cavity and omentum. Issue 4 (2nd September 2020) - Liu, Mingyong; Silva‐Sanchez, Aaron; Randall, Troy D.; Meza‐Perez, Selene
Abstract: The peritoneal cavity is a fluid filled space that holds most of the abdominal organs, including the omentum, a visceral adipose tissue that contains milky spots or clusters of leukocytes that are organized similar to those in conventional lymphoid tissues. A unique assortment of leukocytes patrol the peritoneal cavity and migrate in and out of the milky spots, where they encounter Ags or pathogens from the peritoneal fluid and respond accordingly. The principal role of leukocytes in the peritoneal cavity is to preserve tissue homeostasis and secure tissue repair. However, when peritoneal homeostasis is disturbed by inflammation, infection, obesity, or tumor metastasis, specialized fibroblastic stromal cells and mesothelial cells in the omentum regulate the recruitment of peritoneal leukocytes and steer their activation in unique ways. In this review, the types of cells that reside in the peritoneal cavity, the role of the omentum in their maintenance and activation, and how these processes function in response to pathogens and malignancy will be discussed. Graphical Abstract: Review on how peritoneal specialized leukocyte populations are supported by fat‐associated lymphoid clusters (FALCs) in the omentum, a unique visceral adipose tissue.